2002
DOI: 10.1038/nbt748
|View full text |Cite
|
Sign up to set email alerts
|

Measuring prions causing bovine spongiform encephalopathy or chronic wasting disease by immunoassays and transgenic mice

Abstract: There is increasing concern over the extent to which bovine spongiform encephalopathy (BSE) prions have been transmitted to humans, as a result of the rising number of variant Creutzfeldt-Jakob disease (vCJD) cases. Toward preventing new transmissions, diagnostic tests for prions in livestock have been developed using the conformation-dependent immunoassay (CDI), which simultaneously measures specific antibody binding to denatured and native forms of the prion protein (PrP). We employed high-affinity recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
200
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(208 citation statements)
references
References 18 publications
2
200
1
1
Order By: Relevance
“…Although most transmission data are consistent with the existence of one single strain [188], there has been variations in either incubation periods, which were conserved on subpassage, or neuropathological features among the transmitted isolates [30,82,117], suggesting straindependent variations. LaFauci et al proposed in particular that strains might differ among the mule deer and elk [117], as previously evidenced with PrP Sc conformation studies [170]. The emergence of two strains has been observed on serial adaptation of CWD inocula to hamsters [163].…”
Section: Strain Diversity In Cwd?mentioning
confidence: 79%
See 1 more Smart Citation
“…Although most transmission data are consistent with the existence of one single strain [188], there has been variations in either incubation periods, which were conserved on subpassage, or neuropathological features among the transmitted isolates [30,82,117], suggesting straindependent variations. LaFauci et al proposed in particular that strains might differ among the mule deer and elk [117], as previously evidenced with PrP Sc conformation studies [170]. The emergence of two strains has been observed on serial adaptation of CWD inocula to hamsters [163].…”
Section: Strain Diversity In Cwd?mentioning
confidence: 79%
“…However a deeper comparison of the isolates through conformation-dependant immunoassay (CDI, Tab. II) identified two distinct populations, one in the elk, and the other in deer [170]. Recently, an alternative 19 kDa pattern has also been observed in diseased elk with leucine at codon 132 [142].…”
Section: Strain Diversity In Cwd?mentioning
confidence: 98%
“…Also, it was recently described that, by using immunohistochemical methods, different scrapie sources could differ in their labeling with different antibodies, including P4 monoclonal antibody (26). Immunological characterization of strains suggesting the existence of PrP conformational differences has already been reported for scrapie-infected hamsters and more recently for bovine transgenic mice infected with BSE or variant CJD by using a conformation-dependent immunological assay of abnormal PrP prior to proteinase K digestion (46,47). Together these data show the usefulness of PrP res immunological characterization, which could allow the demonstration of a greater molecular diversity of scrapie strains than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…In some of these studies, it is not clear whether mule deer and elk possess heterogeneous PrP aggregates (strain mixture), or whether the strains may have developed in the new host. However, Safar et al have reported differing conformational characteristics for PrP Sc from CWD-infected white-tailed deer and elk directly, using a conformation dependent immunoassay (CDI) [71], which supports the existence of CWD strains. The possible existence of CWD strains is perhaps not entirely surprising, considering that there are genetic Prnp differences among deer and elk that could influence PrP Sc conformation [34,36,58].…”
Section: Cwd Strains Among Deer and Elkmentioning
confidence: 98%